The Role of Indonesia’s National Health Insurance Cadre: A Case Study in Bali - Indrayathi, Putu Ayu; Prameswari, Agung Ratih Surya Prameswari; Kolozsvari, Laszlo Robert (International Journal of Engineering and Management Sciences, 2024)
The management of informal sector participants poses the most significant difficulty to universal coverage attempts throughout Indonesia's National Health Insurance era. As a result, in April 2017, BPJS Kesehatan established the JKN Cadre Program. This program intends to expand the number of participants while also improving the collectability of contributions from the informal sector. This study aims to investigate the role of the cadre and explore the supporting, and inhibiting factors of such a program. This study is a qualitative descriptive case study, with data gathered through in-depth interviews. Informants were chosen purposefully. Thematic Analysis was utilized to examine the data, which Source Triangulation subsequently confirmed. The study found that the JKN KIS cadre has five functions, the most important of which is to remind people and collect contributions. Cadre activities included education and outreach, as well as collecting payment arrears receipts. The study also identified three inhibiting and supportive elements for the role of cadre namely individual, environmental, and organisational factors. To reduce unfavourable perceptions of JKN-KIS, it is vital to increase cadre self-actualization, self-esteem, information dissemination, synergy, and quality.